Reassessing and Extending the European Standards of Care for Newborn Health: How to Keep Reference Standards in Line with Current Evidence - Isabel Geiger; Johanna Kostenzer; Valerie Matthäus; on behalf of the ESCNH Chair Committee; Silke Mader; Luc J. I. Zimmermann (MDPI AG, 2024)
The European Standards of Care for Newborn Health (ESCNH) were launched in 2018. After three years, the first standards were reassessed and revised to align with current evidence. Moreover, new standards regarding emerging topics were developed. The aim of this paper is to outline the approach adopted for reassessing, revising and developing new standards for the ESCNH. We established a systematic approach to reassess the ESCNH including a public and an expert consultation. The public consultation was open to all stakeholders for feedback whereas the expert consultation followed a targeted consultation method. For developing new standards, a similar process to the original development was implemented. Overall, 20 standards were reassessed and six standards were developed. For the revision process, 23 experts were involved in the targeted consultation method and 253 questionnaires were completed via the open consultation. We demonstrated a systematic approach to update and extend reference standards, which can be applied by other developers of standards. Thereby, we highlighted that including a public and an expert consultation is crucial to improve quality and to ensure that all stakeholder perspectives are integrated.